Pentingnya Komitmen Penuh Organisasi dan Stakeholders dalam Mewujudkan Inovasi Publik - Herwanto, Trisno Sakti (Jurnal Ilmiah Administrasi Publik, 2015)
Innovation is one of the important issues that are becoming a concern in the public sector. Various forms of public service innovation have been developed in order to provide a better quality of service to the community. Nevertheless, the application of innovation in the public sector often faces big challenges. Furthermore, these challenges ultimately hamper the process of transforming good ideas into innovation. By studying about the process of innovation and its challenges, we find that succesfull innovations in the public sector depend on organizational commitment and stakeholders commitment.